A STUDY OF CHANGES IN THE PROTEIN QUALITY OF RAINBOW TROUT (Salmo gairdneri) IN FROZEN STORAGE - Eko Nurcahya Dewi (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Freezing is an effective method of preservation which can produce high quality foods. However, low temperature applied during processing could results in serious product quality deterioration in particular functional properties of protein. During the freezing process salt concentration increases and the change in pH may cause extensive denaturation of muscle protein. The process of denaturation can be accelerated with a resulting increase in thaw drip loss of tissue. In order to examine protein quality, parameters such as soluble protein, drip loss, and changes in the electrophoretic pattern of sarcoplasmic protein of fish muscle were studied. The fish used in this experiment was rainbow trout (Salmo gairdneri). The fish was filleted and frozen in an airblast freezer for an hour at -30°C. They werecalled “fres quality samples”, whereas the “poor quality” samples were fish fillets that have been kept on ice for 3 days before freezing. The samples were analysed for salt soluble protein, thaw drip, water holding capacity and isoelectric focusing of sarcoplasmic protein at the day and the freezing day storage (5 weeks). There was a decrease of 70% on the “fresh quality” sample from the initial value of 82.8% AND 7.5% the “poor quality” sample from 82.5% on the salt soluble protein. Although the differences were small and there were no significant difference between the two samples, the result suggests that of the protein became denatured during frozen storage (5 weeks). There was an increase from 4.3% to 11.6% in “fresh quality” and 6.9% to 12% in “poor quality” sample. The drop of these values reflect the extent of protein denaturation due to ice crystal formation and cell rupture. Sarcoplasmic protein pattern of both sample were not much different before freezing, however there was a disappearance of some light sarcoplasmic bands in the sample after freezing process. On further storage (5 weeks) the pattern obtained were still nearly the same, but light bands did not correspond exactly in their position.